BetterPhoto basics : the absolute beginner's guide to taking photos like the pros - Miotke, Jim.; Betterphoto.com. (New York : Amphoto Books, 2010)
Absolutely anyone can take better photos! If you can press a button, you can take great pictures. It's as simple as that. Jim Miotke shares tips and tricks to improve your photos right away, no matter what camera you're using. Learn to compose knockout shots, make the most of indoor and outdoor light, and photograph twenty popular subjects, from sunsets and flowers to a family portrait.
Getting ready : a snapshot of the art -- Step 1 : meet your camera modes -- Step 2 : forty absolutely easy tips to instantly improve your photos -- Step 3 : twenty popular photo assignments -- Step 4 : master the light to take your photos further -- Step 5 : aperture, shutter speed, and focal length -- Step 6 : thirteen advanced creative techniques -- Step 7 : Ten easy fixes you can do on your computer -- Additional references.
Includes index.
Keywords: Photography -- Amateurs' manuals